INSTITUTIONALIZATION OF STRATEGIC MANAGEMENT IN LOCAL SELF-GOVERNMENT BODIES: INTER-LEVEL INTERACTION AND MANAGERIAL ACCOUNTABILITY - Oliinyk, Volodymyr; Matveyeva, Maryana; Voskobiinyk, Solomiia (Public Management and Policy, 2026)
The article examines the institutionalization of strategic management in local self-government bodies under conditions of decentralization, wartime challenges, digital transformation, and the growing need for coordinated inter-level interaction. The purpose of the study is to identify the specific features of implementing a strategic management system at the local level and to substantiate mechanisms for distributing managerial accountability among public administration actors. Methods and materials. The methodological basis of the research includes systemic, structural-functional and comparative analysis, as well as methods of generalization and synthesis. These methods made it possible to consider strategic management as a comprehensive instrument for coordinating goals, resources, powers and outcomes of territorial development. It is established that strategic management in local self-government bodies is transforming from formal planning into a mechanism of multi-level governance that combines strategic planning, forecasting, monitoring, performance evaluation, risk management and strategy adjustment. The main forms of inter-level interaction are identified, including coordination of strategic documents, joint financing of development programs, intermunicipal cooperation, digital management systems, consultation mechanisms, and partnership projects between the state and territorial communities. The study reveals key problems of accountability, including unclear distribution of powers, formal monitoring procedures, insufficient transparency of decision-making and low public participation in evaluating strategic management results. It is substantiated that the effectiveness of strategic management depends on the combination of legal, financial, digital and public accountability mechanisms, as well as on the ability of different levels of authority to act coherently in the implementation of strategic decisions.